2022
DOI: 10.3390/healthcare10081409
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Relaxation Techniques for Stroke Survivors with Aphasia: A Feasibility and Acceptability Study

Abstract: Stroke survivors with aphasia (SsWA) tend to experience high levels of anxiety and stress, leading to an increased risk of recurrent strokes. Mindfulness and/or relaxation that does not require language outputs could reduce psychosocial stress; however, these approaches work best if they consist of a range of techniques and are modified to suit the needs of SsWA. Using a mixed-methods approach, we examined the feasibility and acceptability of a set of tailored mindfulness and relaxation techniques for SsWA. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This is vital as in previous research survivors with post-stroke aphasia are often excluded from rehabilitation studies [54]. The current PPI findings also support [50] who demonstrated that if study materials are tailored and made as accessible as possible, aphasic survivors are able to contribute to the research project.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is vital as in previous research survivors with post-stroke aphasia are often excluded from rehabilitation studies [54]. The current PPI findings also support [50] who demonstrated that if study materials are tailored and made as accessible as possible, aphasic survivors are able to contribute to the research project.…”
Section: Discussionsupporting
confidence: 78%
“…For example, breath watch has been considered a relaxation technique by Benson and Klipper (2000) [49]. Body relaxation is based on the principles of autogenic relaxation which had been tailored to stroke survivors' needs in previous studies [38,50]. The four techniques were selected and tailored for use with stroke survivors and those with communication difficulties [38].…”
Section: The Current Interventionmentioning
confidence: 99%
“…This burden of thought can cause feelings of stress and trigger a stroke [36]. The link between stress and stroke is significantly correlated and undeniable [37]. First, stress can cause the heart to work harder, raise blood pressure, and increase blood sugar and fat levels.…”
Section: Resultsmentioning
confidence: 99%
“…Further, a reduction in depression scores was evident in those with anxiety after stroke who received the training (22). Supporting the opportunity relaxation proposes for treatment of those with reduced communication ability after stroke, there is evidence relaxation training is acceptable to those with aphasia after stroke (23) and it has been found to impact an observational measure of anxiety with this population (24). It is notable relaxation training is considered an appropriate intervention at both Step 1 and Step 2 of stepped care for mental health post stroke (16).…”
Section: Introductionmentioning
confidence: 83%